REIMAGINING ARCHITECTURE THROUGH DECOLONIAL LENSES: INSIGHTS FROM SMITH, TUCK, AND YANG - Ayu Putu Utari Parthami Lestari; Made Ratna Witari; I Gede Gandhi Silantara; Made Prarabda Karma (Architectural Research Journal, 2024)
Westernisation in architectural education, in particular, has for a long time eroded indigenous people’s appreciation of building and design. This study reintroduces decolonization into architectural discourse by analyzing two key frameworks: Smith’s Decolonizing Methodologies and the decolonial theoretical framework by E. Tuck and Wayne Yang. In doing so, the work discusses whether these frameworks are useful in deconstructing and diversifying architectural practices against Eurocentric epistemologies. It shows that the colonial mindset in architectural design has not changed and this paper underscores the necessity of integrating Indigenous peoples’ knowledge for culturally appropriate and socially sustainable development. Co-authored by architecture students and professionals, this study maps out how decolonial architectural education and practice are possible. The research therefore is pleading for change in the wheels through the deconstruction of the dominant paradigm and an emancipation of the subordinate voices to perform an art of makeover on the existing architectural constructs.